What Difference Does a Lawyer Make? Impacts of Early Counsel on Misdemeanor Bail Decisions and Outcomes in Rural and Small Town Courts - Worden, Alissa Pollitz (Criminal justice policy review, 2018)
Recent court decisions and state legislation have highlighted the significance of ensuring that criminal defendants are represented by counsel at their first appearances in court, where judges make critical decisions on pretrial release, bail, and detention. Yet many jurisdictions do not routinely provide counsel to indigent defendants at this stage. We hypothesize that when defendants are represented by counsel at first appearance (CAFA), they are more likely to be released on recognizance, are less likely to have high bail set, and are consequently less likely to be jailed pending disposition. We explore the impact of lawyers’ presence by comparing pretrial decisions and bail outcomes across samples of misdemeanor cases in three rural counties in upstate New York: cases with and without CAFA. We find that these counties saw shifts in decisions or outcomes. We consider the implications of these findings for future research, court practices, and public policy.